Prospects and Problems of Women Entrepreneurs in and Around Coimbatore City - Ramesh, Mr. (Journal of Contemporary Research in Management (JCRM), 2013)
The topical world is not only in spherical profile but also hectic with business. Hence it is obvious that if we want to endure in this tropical planet holding our own business units intact, we have to have acquaintance in various areas like Commerce, Marketing, Management, Finance etc. irrespective of the gender. Now a days female groups are equivalent to male groups in all aspects. In order to ensure this, the mobs of female are engaged in doing their own business also. This study isÂ focused on the various issues faced by women entrepreneurs in carrying out their own businesses in spite of their family commitments. The study covers the supports offered to women entrepreneurs from their ownÂ families and government(s) to stand on their own legs to face the challenges in this world. The study has proved that the female entrepreneurs are not only helpful to their own families but they are alsoÂ useful to the society or nation as a whole after analyzing the relevant data and drawing the conclusion.